Gambaran Kecemasan dan Depresi pada Pasien Dengan Kanker Ginekologi di RSUP Dr. Hasan Sadikin Bandung - Retnowulan, Veha; Maryati, Ida; Ermiati, Ermiati (Universitas Malahayati, 2025)
ABSTRACT Anxiety and depression are common psychological problems in gynecological cancer patients. Symptoms of anxiety and depression not only affect the patient's mental health but also their quality of life. High levels of anxiety and depression can worsen health and slow down the healing process. This study aims to determine the description of anxiety and depression in gynecological cancer patients at Dr. Hasan Sadikin General Hospital, Bandung. The quantitative descriptive study design with purposive random sampling of gynecological cancer patients at the Obstetrics and Gynecology Polyclinic, Dr. Hasan Sadikin General Hospital, Bandung (N=79). The instrument used was the Hospital Anxiety and Depression Scale (HADS), analyzed using univariate descriptive statistics. Data collection was carried out from November-December 2024. The results of this study indicate that almost all respondents have abnormal anxiety levels (86.08%), only a small portion of patients (2.53%) have normal anxiety levels and abnormal borders (11.39%). As for the level of depression, almost half of the respondents (49.37%) had an abnormal borderline depression level and a small portion of respondents 0-7 (21.52%) had an abnormal depression level. It can be concluded that the level of anxiety in gynecological cancer patients is abnormal and the level of borderline depression is abnormal with almost all of the respondents (83.54%) being in adulthood, namely 15-59 years old and having a final education level of elementary education (59.5%) which affects their psychological state. Nurses can carry out specific interventions, one of which is providing education as early as possible to patients with gynecological cancer. Keywords: Cancer, Gynecology, Anxiety, Depression ABSTRAK Kecemasan dan depresi merupakan masalah psikologis umum pada pasien kanker ginekologi. Gejala kecemasan dan depresi tidak hanya memengaruhi kesehatan mental pasien tetapi juga kualitas hidup. Tingkat kecemasan dan depresi yang tinggi dapat memperburuk kesehatan dan memperlambat proses penyembuhan. Penelitian ini bertujuan mengetahui gambaran kecemasan dan depresi pasien kanker ginekologi di RSUP Dr. Hasan Sadikin Bandung. Rancangan penelitian deskriptif kuantitatif dengan purposive random sampling pasien kanker ginekologi di Poli Kandungan dan Kebidanan RSUP Dr. Hasan Sadikin Bandung (N=79). Instrumen yang digunakan adalah Hospital Anxiety and Depression Scale (HADS), dianalisis dengan deskriptif statistic univariat. Pengambialn data dilakukan dari bulan November-Desember 2024. Hasil penelitian ini menunjukkan bahwa hampir seluruh dari responden memiliki tingkat kecemasan abnormal (86,08%), hanya sebagian kecil dari pasien (2,53%) yang memiliki tingkat kecemasan normal dan boderline abnormal (11,39%). Sedangkan untuk tingkat depresi, hampir setengahnya dari responden (49,37%) memiliki tingkat depresi borderline abnormal dan sebagian kecil dari responden 0-7 (21,52%) memiliki tingkat depresi abnormal. Dapat disimpulkan tingkat kecemasan pasien kanker ginekologi abnormal dan tingkat depresi borderline abnormal dengan hampir seluruh dari responden (83,54%) berada pada usia dewasa yaitu 15-59 tahun dan memiliki tingkat pendidikan terakhir pendidikan dasar (59,5%) yang berpengaruh terhadap keadaan psikologisnya. Perawat dapat melakukan intervensi yang spesifik salah satunya dapat berupa edukasi sedini mungkin pada pasien dengan kanker ginekologi. Kata Kunci: Kanker, Ginekologi, Kecemasan, Depresi